The Role of Islamic Podcast in Forming Religious Attitudes of the Young Generation in Tulus Rejo Village Pekalongan District - Ayu Wulandari; Dedi Setiawan; Muhammad Syaifullah (CV. Creative Tugu Pena, 2025)
This study aims to examine the role of Islamic podcasts in shaping the religious attitudes of young people in Tulus Rejo Villagee, Pekalongan District. In the digital era, podcasts have emerged as an alternative medium for religious learning and da’wah due to their accessibility, flexibility, and relevance to the lifestyle of modern youth. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and documentation involving selected youth participants who actively engage with Islamic podcast content. The findings reveal that Islamic podcasts play four significant roles: educative, inspirational, social and da’wah, and transformational. From an educative perspective, podcasts enhance the understanding of Islamic teachings in a more accessible and flexible manner. From an inspirational perspective, they motivate individuals to improve their religious practices and self-awareness. Socially, podcasts promote Islamic values such as empathy, respect, and social responsibility. Most importantly, the study identifies a transformational impact, where continuous exposure to podcast content leads to observable changes in behavior and the internalization of religious values among youth. The novelty of this study lies in its emphasis on the transformational dimension of digital religious media, particularly within a rural context, which remains underexplored in existing literature. The study also highlights three key factors influencing the effectiveness of Islamic podcasts: accessibility, relatability, and continuity. This study concludes that Islamic podcasts are an effective medium for religious education and digital da’wah, offering a relevant and innovative approach to engaging young audiences in the contemporary digital era.